One‐pot green synthesis and structural characterisation of silver nanoparticles using aqueous leaves extract of Carissa carandas : antioxidant, anticancer and antibacterial activities. Issue 6 (1st May 2018) - Singh, Deepika; Kumar, Vikas; Yadav, Ekta; Falls, Neha; Singh, Manvendra; Komal, Ujendra; Verma, Amita
Abstract : Facile green synthesis of silver nanoparticles (AgNPs) using an aqueous extract of Carissa carandas ( C. carandas ) leaves was studied. Fabrication of AgNPs was confirmed by the UV–visible spectroscopy which gives absorption maxima at 420 nm. C. carandas leaves are the rich source of the bioactive molecules, acts as a reducing and stabilising agent in AgNPs, confirmed by Fourier transforms infrared spectroscopy. The field emission scanning electron microscope revealed the spherical shape of biosynthesised AgNPs. A distinctive peak of silver at 3 keV was determined by energy dispersive X‐ray spectroscopy. X‐ray diffraction showed the facecentred cubic structure of biosynthesised AgNPs and thermal stability was confirmed by the thermogravimetric analysis. Total flavonoid and total phenolic contents were evaluated in biosynthesised AgNPs. Biosynthesised AgNPs showed free radical scavenging activities against 2, 2‐diphenyl‐1‐picrylhydrazyl test and ferric reducing antioxidant power assay. In vitro cytotoxicity against hepatic cell lines (HUH‐7) and renal cell lines (HEK‐293) were also assessed. Finally, biosynthesised AgNPs were scrutinised for their antibacterial activity against methicillin‐resistant Staphylococcus aureus, Shigella sonnei, Shigella boydii and Salmonella typhimurium . This study demonstrated the biofabrication of AgNPs by using C. carandas leaves extract and a potential in vitro biological application as antioxidant, anticancer and antibacterial agents.